Effect of Group Therapy Promotion on of Psychological wellbeing among Elderly at Selected Old Age Home - Sheetal Barde (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to assess the effect of Group therapy on promotion of psychological well-being amongelderly at selected old age homes in Pune. The investigators adopted the Experimental design for the study.The participants were 60 elderly from selected Old Age Home from Pune. Random Assignment techniquewas used to select the sample. The instrument consisted of two sections. Study has shown significance at0.05 levels and found group therapy is effective for improving Psychological wellbeing among elderly